Awareness and Attitude Regarding Complementary and Alternative Medicine among Middle Aged Adults - Aryal, Isha; Adhikari, Sarita (Journal of Nepal Health Research Council, 2021)
Background: Complementary and Alternative Medicine is a group of diverse medical and health care practices and products that are not presently considered to be part of conventional medicine. The purpose of study was to assess the level of awareness and attitude of Complementary and Alternative medicine among middle aged adults and to find out the correlation between awareness and attitude.Methods: A descriptive, correlational study design was carried out on 63 subjects through convenient sampling technique. Data was collected through face to face interview method among middle aged adults of Kirtipur municipality in Kathmandu by using Nepali version of structured set of questionnaire for all respondents. Data were entered using SPSS-20 and analyzed using descriptive statistics for socio-demographic and study variables, and inferential statistics namely Spearman Rank correlation coefficient was used to assess the relation between awareness and attitude regarding Complementary and Alternative medicine. Results: Highest proportion (36.5%) of respondents was aged from 41-45 years. Majority (88.9%) of the respondents were literate. It was found that majority (71.4%) of the middle aged adults pose moderate knowledge and favorable attitude (93.7%) regarding complementary and alternative medicine, with negligible relationship between awareness and attitude(r=0.171).Conclusions: This study concluded that majority of the middle aged adults pose moderate knowledge and favorable attitude regarding complementary and alternative medicine, with negligible relationship between awareness and attitude. Keywords: Attitude; wwareness; complementary and alternative medicine; middle aged adults